2017
DOI: 10.1038/ismej.2017.48
|View full text |Cite
|
Sign up to set email alerts
|

Warming enhances old organic carbon decomposition through altering functional microbial communities

Abstract: Soil organic matter (SOM) stocks contain nearly three times as much carbon (C) as the atmosphere and changes in soil C stocks may have a major impact on future atmospheric carbon dioxide concentrations and climate. Over the past two decades, much research has been devoted to examining the influence of warming on SOM decomposition in topsoil. Most SOM, however, is old and stored in subsoil. The fate of subsoil SOM under future warming remains highly uncertain. Here, by combining a long-term field warming experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(114 citation statements)
references
References 46 publications
9
96
0
1
Order By: Relevance
“…This method differed from the majority of previous studies, in which soil temperature was elevated through heating surface air and/or topsoil layers to simulate the magnitude of rise in surface air temperature (2,3). Although it is expected that ongoing and future air warming would increase the temperature of the soil profile, the magnitude of temperature elevation likely attenuates with depth.…”
Section: H Icks Pries Et Almentioning
confidence: 79%
See 1 more Smart Citation
“…This method differed from the majority of previous studies, in which soil temperature was elevated through heating surface air and/or topsoil layers to simulate the magnitude of rise in surface air temperature (2,3). Although it is expected that ongoing and future air warming would increase the temperature of the soil profile, the magnitude of temperature elevation likely attenuates with depth.…”
Section: H Icks Pries Et Almentioning
confidence: 79%
“…They found that a 2-year in situ warming of 4°C significantly enhanced the whole-soil CO 2 production by 34 to 37%, and that all soil layers exhibited similar temperature sensitivity with a mean apparent Q 10 of 2.7 ± 0.3. We argue that although the idea of subsoil carbon dynamics in response to warming is worth testing (2, 3), their conclusions are critically undermined by the experimental approach and analysis.…”
Section: H Icks Pries Et Almentioning
confidence: 99%
“…Our finding of a warming‐induced increase in ligninase activity relative to cellulase activity indicates soil microbes decompose more chemically complex and recalcitrant C pools (e.g., lignin) to fuel their metabolic processes (Romero‐Olivares et al, ; Sinsabaugh, ). Indeed, several recent studies found that warming favors microbial functional communities degrading old and recalcitrant C pools (Cheng et al, ; Feng et al, ; Woodcroft et al, ; Xue et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous meta-analyses across multiple terrestrial ecosystems (Lu et al, 2013;Rustad et al, 2001;Wang et al, 2014), our study also reported that warming-induced changes in ANPP, NPP, NEE and GPP were negatively correlated with MAT (Table 1) Cold grasslands were expected to be generally more limited by temperature than by water compared to semi-arid and temperate grasslands, and should benefit the most from longer snow-free and growing seasons associated with warming (e.g., Price, Waser, Ecology, & Jun, 1998). In addition, warming is likely to increase the microbial decomposition of soil organic matter (e.g., Crowther et al, 2016, Cheng et al, 2017 and N mineralization (e.g., Bai et al, 2013;Liu et al, 2017;Rustad et al, 2001), thus alleviating nutrient limitations and stimulating plant N uptake, particularly for cold grassland soils, which are characterized by the highest SOC contents. Only in cold grasslands did the responses of Rs, ANPP and BNPP significantly increase with warming magnitude (Table S1), suggesting that neither heat stress nor nutrient limitation of plant growth was confounding warming effects in these ecosystems.…”
Section: Variation In Grassland C Flux Responses To Warmingmentioning
confidence: 99%